The effectiveness of Bacillus-coated NPK fertilizer on broccoli growth, nutrient status, rhizosphere Bacillus population, yield, and flower quality - Fitriatin, Betty Natalie; Risanti, Rara Rahmatika; Hindersah, Reginawanti; Hanindipto, Fasa Aditya; Nugraha, Gita Bina (Kultivasi, 2026)
Efforts to increase the availability of macronutrients in soil have relied on inorganic fertilization, particularly NPK fertilizers. However, global challenges in the fertilizer raw material supply chain, including price fluctuations and availability, are driving the need for more efficient and sustainable fertilizer alternatives.  The  field experiment was conducted in Baruajak, Lembang District, West Java, Indonesia, to evaluate the effectiveness of Bacillus-coated NPK fertilizer on broccoli (Brassica oleracea var. italica) growth, nutrient status, rhizosphere Bacillus population, yield, and flower quality. The experiment used a randomized complete block design with 15 fertilizer treatments and three replications. Treatments consisted of two coated NPK formulations, Formula C (0.4% Bacillus consortium + 0.2% zeolite) and Formula G (0.2% Bacillus consortium + 0.4% zeolite), applied once or twice at 100%, 75%, and 50% of the recommended NPK dose, and conventional NPK fertilizer at the same dose levels. The recommended NPK dose for broccoli was 300 kg ha⁻¹. Plant growth, chlorophyll content, shoot biomass, nutrient concentration and uptake, soil nutrient status, rhizosphere Bacillus population, flower yield, flower diameter, and vitamin B3 and K contents were observed. The results showed that Bacillus-coated NPK fertilizer generally improved vegetative growth compared with conventional NPK fertilizer. Formula G applied once at 100% recommended NPK dosage produced the highest flower weight and diameter, while Formula C applied once at 75% resulted in the highest vitamin B3 and vitamin K contents. The coated NPK fertilizer maintained shoot N, P, and K concentrations comparable to those of conventional NPK and showed potential to partially or fully replace conventional NPK in broccoli cultivation.